PEMBUDIDAYAAN JAMUR TIRAM PADA SERBUK GERGAJI DARI LIMA JENIS KAYU - Sihati Suprapti (Jurnal Penelitian Hasil Hutan, 1988)
The  result   of  oyster   mushroom  (Pleurotus   ostreatus) cultivation    on  sawdust    of  five  wood  species  i.e. jeungjing (Albizia  falcataria   (L.) Foeb.),   rubber (Hevea brasiliensis Muell.  Arg. ), pulai (Alstonia  scholaris R.Br.),  pine  (Pinus merkusii Jungh  et  De  Vr.) and weru (Albizia  procera  Benth) is reported  in this paper.   The  compositions   of  the  media  were 97.5 % sawdust,  92.5 % sawdust +  5 % rice bran, 87.5  %  sawdust +10 % rice bran,  82.5 % sawdust+   15  % rice bran,  and 77.5 % sawdust   +  20 %  rice bran.  Each  of  the  media  was mixed  with  1.5 % gypsum,  0.5  % three superphosphate  (TSP), 0.5% lime  and  sufficient  distilled   water.  The  media  was allowed  to cool after  sterilization   before   being  inoculated   with  pure culture  of mushroom.   The mature  mushroom   were harvested  daily after  the growth  of fruiting  body. The media start producing  fungus  two  months  after  inoculation. The mean yield  of entire  treatments were obtained from  rubber: 225.86 g (146  - 261.8  g), weru  : 199.28 g (23.2  - 264. 7 g),  pulai: 162.4 g (67.2 - 231.2 g),  jeungjing  : 142.73 g  (33.6 -  236.8 g) and pine  : 80.97g (0 -   161.6 g) per  500  g media. The yield  of  mushroom   cultivated.  in PVC plastic bag was  better  than  that  using HD plastic  bag. The  rice bran supplement   seems  to improve  mushroom yield. The  average  Biological  Efficiency of  entire  treatments   were  obtained   from weru  :   90.83%  (11.82-122.38  %), rubber: 88.11  % (58.04  -104.07%),  pulai: 87.61%  (39.38-121.38     %),  jeungjing : 73.74   % (22.76-118.4 %),  and pine  :   28.62  % (0 - 60.6  %).